Analysis of the Influence of Macroeconomic and Global Factors on the Composite Stock Price Index on the Indonesia Stock Exchange - Said, Neysa Khairina Nur (Bulletin of Islamic Economics, 2023)
Fluctuations in the movement of the Composite Stock Price Index are caused by the influence of macroeconomic and global factors. Looking at the inconsistencies in the results of previous research, the significance of the influence is still questionable. In this context, this study aims to analyze the Influence of Macroeconomic Factors with indicators of Inflation and Money Supply, as well as Global Factors with indicators of World Oil Prices with the Error Correction Model (ECM) approach. Using research observations from 2021-2023, it was found that the variables Inflation, Money Supply and World Oil Price have a long-term influence on the Composite Stock Price Index on the IDX, while in the short term, only the World Oil Price variable influences the Composite Stock Price Index on the JCI.